Bloodstream infections in critically ill patients with COVID‐19. (11th August 2020) - Giacobbe, Daniele Roberto; Battaglini, Denise; Ball, Lorenzo; Brunetti, Iole; Bruzzone, Bianca; Codda, Giulia; Crea, Francesca; De Maria, Andrea; Dentone, Chiara; Di Biagio, Antonio; Icardi, Giancarlo; Magnasco, Laura; et al.
Abstract: Background: Little is known about the incidence and risk of intensive care unit (ICU)‐acquired bloodstream infections (BSI) in critically ill patients with coronavirus disease 2019 (COVID‐19). Materials and methods: This retrospective, single‐centre study was conducted in Northern Italy. The primary study objectives were as follows: (a) to assess the incidence rate of ICU‐acquired BSI and (b) to assess the cumulative risk of developing ICU‐acquired BSI. Results: Overall, 78 critically ill patients with COVID‐19 were included in the study. Forty‐five episodes of ICU‐acquired BSI were registered in 31 patients, with an incidence rate of 47 episodes (95% confidence interval [CI] 35‐63) per 1000 patient‐days at risk. The estimated cumulative risk of developing at least one BSI episode was of almost 25% after 15 days at risk and possibly surpassing 50% after 30 days at risk. In multivariable analysis, anti‐inflammatory treatment was independently associated with the development of BSI (cause‐specific hazard ratio [csHR] 1.07 with 95% CI 0.38‐3.04 for tocilizumab, csHR 3.95 with 95% CI 1.20‐13.03 for methylprednisolone and csHR 10.69 with 95% CI 2.71‐42.17 for methylprednisolone plus tocilizumab, with no anti‐inflammatory treatment as the reference group; overall P for the dummy variable = 0.003). Conclusions: The incidence rate of BSI was high, and the cumulative risk of developing BSI increased with ICU stay. Further study will clarify if the increased risk of BSI we detected in COVID‐19 patients treated with anti‐inflammatory drugs is outweighed by the benefits of reducing any possible pro‐inflammatory dysregulation induced by SARS‐CoV‐2.